A qualitative evaluation of the national rollout of a diabetes prevention programme in England - Peter Bower; Claudia Soiland-Reyes; Carole Bennett; Lisa Brunton; Patrick Burch; Elaine Cameron; Tarani Chandola; Georgia Chatzi; Sarah Cotterill; David P French; Judith Gellatly; Mark Hann; et al. (Health and Social Care Delivery Research, 2025)
This article consists of a citation of a published article describing research funded by the Health and Social Care Delivery Research programme under project number 16/48/07, and is provided as as part of the complete record of research outputs for this project. The original publication is available at: https://doi.org/10.1186/s12913-023-10002-y Background The National Health Service Diabetes Prevention Programme (NHS DPP) was commissioned by NHS England in 2016 and rolled out in three ‘waves’ across the whole of England. It aims to help people with raised blood glucose levels reduce their risk of developing type 2 diabetes through behaviour change techniques (e.g., weight loss, dietary changes and exercise). An independent, longitudinal, mixed methods evaluation of the NHS DPP was undertaken. We report the findings from the implementation work package: a qualitative interview study with designated local leads, responsible for the local commissioning and implementation of the programme. The aim of the study was to explore how local implementation processes were enacted and adapted over time. Methods We conducted a telephone interview study across two time-points. Twenty-four semi-structured interviews with local leads across 19 sampled case sites were undertaken between October 2019 and January 2020 and 13 interviews with local leads across 13 sampled case sites were conducted between July 2020 and August 2020. Interviews aimed to reflect on the experience of implementation and explore how things changed over time. Results We identified four overarching themes to show how implementation was locally enacted and adapted across the sampled case sites: 1. Adapting to provider change; 2. Identification and referral; 3. Enhancing uptake in underserved populations; and 4. Digital and remote service options. Conclusion This paper reports how designated local leads, responsible for local implementation of the NHS DPP, adapted implementation efforts over the course of a changing national diabetes prevention programme, including how local leads adapted implementation during the COVID-19 pandemic. This paper highlights three main factors that influence implementation: the importance of facilitation, the ability (or not) to tailor interventions to local needs and the role of context in implementation. Funding This publication was funded by the Health and Social Care Delivery Research programme as a part of award number 16/48/07. DOI https://doi.org/10.1186/s12913-023-10002-y This article reports on one component of the research award Evaluating the NHS Diabetes Prevention Programme (NHS DPP): the DIPLOMA research programme (Diabetes Prevention Long term Multimethod Assessment). For more information about this research please view the award page [https://fundingawards.nihr.ac.uk/award/16/48/07]